An Interdisciplinary University-Based Initiative for Graduate Training in Evidence-Based Treatments for Children's Mental Health. (March 2016) - Kerns, Suzanne E. U.; Cevasco, Molly; Comtois, Katherine A.; Dorsey, Shannon; King, Kevin; McMahon, Robert; Sedlar, Georganna; Lee, Terry G.; Mazza, James J.; Lengua, Liliana; Davis, Carol; Evans-Campbell, Tessa; et al.
States and jurisdictions are under increased pressure to demonstrate the use of evidence-based treatments (EBTs) for children's mental health, increasing the demand for a workforce trained in these practices. Universities are a critical pipeline for this workforce. This article describes the genesis and evolution of a university-based initiative for training in EBTs for children, youth, and families. Given both the need to make training in EBTs available to future providers in a range of disciplines and that mental health providers increasingly find themselves on interdisciplinary teams (despite university-based training being relatively siloed along disciplinary lines), the initiative has had an interdisciplinary focus. Two tracks are described: (a) Practitioner Track, a course series in which students learn a specific EBT, and (b) Referral Track, a monthly lecture series designed to engage a wider university and community audience. Results of the program evaluation component of this initiative revealed that students can significantly increase their skills and self-efficacy in components of EBT delivery through participation in the active, skill-focused courses. Furthermore, the results of the lecture series evaluation appear to meet an important need for community-based providers and other supportive individuals in transferring useful knowledge about best practices. Implications and future directions are discussed.